A growth-related mRNA in cultured mouse cells encodes a placental calcium binding protein. - Jackson-Grusby, L L (1987)
We have characterized an mRNA that increases in abundance after serum stimulation of quiescent mouse fibroblasts. This mRNA, designated 18A2, encodes a predicted polypeptide of 101 amino acids with homology to known calcium binding proteins. A variety of mouse tissues express the 18A2 mRNA, with the highest levels detected in the non-pregnant uterus and in the placenta. The concentration of 18A2 mRNA in total placental RNA decreases from day 8 to day 10 of pregnancy, and is below detection throughout the latter half of gestation. In serum-stimulated fibroblasts, the increase in 18A2 mRNA is dependent on protein synthesis. The 18A2 mRNA is similar in size, serum-inducibility, and sequence to the 2A9 mRNA (1), but these mRNAs are derived from distinct genes. This suggests that the mouse genome harbors a family of serum-inducible genes encoding proteins predicted to bind calcium.